Improving Students’ Speaking Ability through Story Completion Technique in Narrative Text - Khoiriyah Shofiyah Tanjung; Rahmadhani Fitri (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This research aims to find out how to improve students’ speaking ability by using Story Completion Technique. The writers applied Collaborative Classroom Action Research as the method of research, where there are four steps that must be followed, they are: planning, action, observation and reflection. In this research, the writers only conducted one cycle due to the fact that the result of the test has been successful. There are 30 eighth grader students of SMPN 1 Takengon as the sample of this research. The data were taken from observation and students’ speaking test in pre-test and post-test, then were analyzed quantitatively. The result of the cycle was described qualitatively. From the results of the research, it was found that using Story Completion Technique in speaking lesson was very enjoyable and it encouraged students to speak more fluently. It can be proven from the result of pretest and posttest, which showed that the posttest score is higher than that of the pre-test (2204 for the pretest and 1640 for the posttest). That means the pre-test score is 54.67 and the post-test score is 73.47.